Monitoring of Aquatic Environmental Factors on the Growth of Whiteleg Shrimp (Litopenaues vannamei Boone, 1931) - Muhammad Akbarurrasyid; Ega Aditya Prama; Kennedi Sembiring; Meliana Anjarsari; Achmad Sofian; Wahyu Puji Astiyani (Jurnal Perikanan Universitas Gadjah Mada, 2023)
The environment is an important aspect and can be an indicator of the success of whiteleg shrimp culture. Stable water quality is a condition when water quality meets the requirements of growing whiteleg shrimp. This study aims to determine the aquatic environmental factors on the growth of whiteleg shrimp. There were 3 ponds observed in this research with an area of 2.000 m2, 2.500 m2, and 350 m2 respectively. The result of the research shows that the water quality of whiteleg shrimp culture is still in the feasible category. Several parameters show fluctuated results beyond optimal values such as dissolved oxygen, salinity, total ammonia nitrogen, and total organic matter. The results of the correlation test showed that all the quality parameters of whiteleg shrimp culture had varying degrees of relationship. The highest correlation level was obtained in salinity, nitrate, nitrite, ammonia, temperature, and dissolved oxygen. Water quality in each pond has a very strong relationship to the growth of mean body weight (10.31 g, 10.92 g, and 11.39 g), average daily growth (0.4142 g, 0.4971 g, and 0.3557 g), and survival rate (92.4%, 92.4%, and 92.3%).